2016
DOI: 10.1186/s12877-016-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants with dementia in Swedish residential care: an exploratory study of the experiences of their family members and Nursing staff

Abstract: BackgroundWorldwide, there is a growing population of older people who develop dementia in a country other than that of their origin. When their dementia has reached an advanced stage, residential care is most often needed. People with dementia in Sweden are often cared for in group homes. For immigrants, this may mean a linguistically challenging care environment for both healthcare staff and the patients’ family members.The aim of this study was to explore and describe the experiences of family members and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…The studies reported serious misunderstandings between staff members and older persons and that staff was not able to recognize what older persons needed nor could they deliver needed care. 42 , 43 Canadian researchers indicated that ethnicity and culture should be addressed to improve situations for care recipients and home care staff. 44 …”
Section: Discussionmentioning
confidence: 99%
“…The studies reported serious misunderstandings between staff members and older persons and that staff was not able to recognize what older persons needed nor could they deliver needed care. 42 , 43 Canadian researchers indicated that ethnicity and culture should be addressed to improve situations for care recipients and home care staff. 44 …”
Section: Discussionmentioning
confidence: 99%
“…This study is a part of a larger study entitled “ Ethnic minority people with dementia being cared for in special accommodation in Sweden ”. The data was collected during a period of one year which also included interviews with relatives and AN (Rosendahl et al 2016 ). An observational study with a qualitative approach and a qualitative, deductive content analysis method was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Older bilinguals often revert to a single language despite a lifetime of dual language use, losing the ability to speak the second language [26]. This issue is particularly prominent among migrants and refugees with dementia who lose their ability to speak their second languages, which is often the language of their host country, leading to difficulty in communicating with the health-care professionals and service providers [27]. Bilingual individuals with dementia are frequently observed to be inclined to asymmetrical language impairment with preferential preservation and the use of the first acquired language [28], which can be inferred among individuals that have migrated to a foreign country that speaks a different language than one's country of emigration.…”
Section: Language Barriermentioning
confidence: 99%
“…Evidence obtained from the study of immigrants in Sweden suggested that immigrants with dementia noticeably preferred music and television programs that had more familiarity, such as programs in their native language [27]. They were also more likely to participate and engage in dementia support programs and services where they could communicate in their native language [23,26].…”
Section: Language Barriermentioning
confidence: 99%